The Philosophy of Criticism in Ibn Rushd and the Possibility of Civilizational Revival: A Comparative Analytical Study - Alsaied, Mohamad Abdullah (Journal of Ecohumanism, 2024)
This research has dealt with an important issue in the history of Islam mainly from to angles. The first one is to reveal the importance of the intellectual projects this nation. The second is mainly concerned with the way in getting benefits from them at present. This is what I am trying to investigate by following Ibn Ruchd ‘s critical project. His project is mainly represented in the localization of rational approach within religious thought by justifying the legitimacy of philosophical rational proofs to explore the value of religious knowledge. Also, this philosopher has confronted theological principles through the great critical work as an attempt to restore the presence of philosophy in the intellectual field after Al Ghazali directed as a strong stab at it that shook its theoretical foundations. This study is devided into three major parts. In fact, after giving a brief definition of Ibn Rochd, I will deal not only with the dominance of the Ashaari trend and the emergence of critical school of Ibn Rochd but also I will concentrate on the establishment of the Islamic mind. In this work, I have dealt with objectivity and subjectivity in Ibn Rochd’s critical philosophy and the man’s ability to localize the rational approach with Islamic thought. Then, I wondered about the possibilities of drawing inspiration from the rational approach to restore the potential for civilized revival.